2012
DOI: 10.1021/jp306107t
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Dealloyed PtCo3and PtCu3Cathode Catalysts for Proton Exchange Membrane Fuel Cells

Abstract: Dealloyed PtCo 3 and PtCu 3 catalysts supported on high surface area carbon (HSC), which were synthesized under different conditions, were tested as cathode electrodes in proton exchange membrane fuel cells. The dealloyed PtCu 3 / HSC gave higher initial oxygen reduction reaction (ORR) kinetic activity but much worse durability in a voltage cycling test. Detailed characterization was undertaken to develop insights toward the development of catalysts with both high activity and good durability. In situ X-ray ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
118
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(135 citation statements)
references
References 29 publications
12
118
0
5
Order By: Relevance
“…However, their stability is still under debate and is the topic of many current and future studies [13][14][15][16][17][18][19][20]. Three issues are foreseen for Ptalloys: (i) loss of initially superior ORR activity [13], (ii) formation of unstable porous nanoparticles [9,15] and (iii) poisoning of the PEM FC by the leached less noble metal cations [12,[21][22][23]. It is known that leached metals can cause the increase of the resistance of the polymer membrane and the lowering of the performance of the anode electrocatalysts due to the poisoning of the Pt surface [12,23].…”
Section: Introductionmentioning
confidence: 99%
“…However, their stability is still under debate and is the topic of many current and future studies [13][14][15][16][17][18][19][20]. Three issues are foreseen for Ptalloys: (i) loss of initially superior ORR activity [13], (ii) formation of unstable porous nanoparticles [9,15] and (iii) poisoning of the PEM FC by the leached less noble metal cations [12,[21][22][23]. It is known that leached metals can cause the increase of the resistance of the polymer membrane and the lowering of the performance of the anode electrocatalysts due to the poisoning of the Pt surface [12,23].…”
Section: Introductionmentioning
confidence: 99%
“…28 for Pt and 1.90 for Cu) [41,42], and the shortening in the Pt-Pt bond lengths [37]. Both effects contribute to change the d-states electronic population, and hence affects the oxygen binding energy, as suggested by X-ray absorption spectroscopy analysis on PtCu NPs supported on high surface area carbon [43].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that different thermal treatments caused significant structural and morphological modifications in the PtCo catalysts. Yu et al studied the cycling stability of dealloyed PtCo 3 and PtCu 3 catalysts between 0.6 and 1.0 V (vs. RHE) for up to 30,000 cycles [38]. In situ X-ray absorption spectroscopy (XAS) analysis showed stronger bulk Pt-Pt compressive strains and higher bulk d-band vacancies for the dealloyed PtCu 3 than the dealloyed PtCo 3 which was correlated to the higher initial activity of dealloyed PtCu 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In general, PtM 3 (M = Cu, Co, Ni, Fe, Cr) catalysts are prepared by impregnating excess amount of transition metal salts into Pt/C catalyst followed by a heat-treatment under a reducing atmosphere and acid leaching procedures [24,38,39]. Since excess transition metal salts are used for the catalyst synthesis, the leaching is carried out in strong acids for prolonged time which may be detrimental to the support stability when the cathode experiences high potentials during startup/shutdown cycles.…”
Section: Introductionmentioning
confidence: 99%